The representation of Syrian refugees in Canadian online news media: a focus on the Topos of burdening - Mustafa, Manar; Pilus, Zahariah; Lotfie, Maskanah Mohammad (PKP Publishing Services, 2021)
Background: This study focuses on the representation of Syrian refugees in Canadian online news media. It examines 375 articles selected from three of the most visited Canadian news sites, namely the Toronto Star, which favours the Liberal Party, and the Toronto Sun and National Post, which favour the Conservative Party. Analysis: The basis of this research is a topoi analysis, whereby instances of the topos of burdening are identiﬁed, examined, and categorized as either positive or negative. Conclusion and implications: A distinction is drawn between the depiction of Syrian refugees in conservative- and liberal-leaning news sources. The ﬁndings aim to provide some insight into the possible impact of media representation on both the Syrian refugees and the Canadian public.